Pathways to rural youth agribusiness success: Stories from the Vijabiz project - Lohento, Ken; Mazuri, George (Technical Centre for Agricultural and Rural Cooperation, 2020)
The different cases or stories presented in this booklet are the results from the experience capitalization exercise and give insights into the specific lessons learnt by the workshop participants, through analysis of their involvement in diverse activities of the Vijabiz project and the influence on their businesses.